Design, synthesis, molecular docking, anti‐quorum sensing, and anti‐biofilm activity of pyochelin‐zingerone conjugate. Issue 4 (4th January 2021) - Nosran, Anu; Kaur, Parleen; Randhawa, Vinay; Chhibber, Sanjay; Singh, Vasundhara; Harjai, Kusum
Abstract: In this article, we report the chemical synthesis of pyochelin‐zingerone conjugate via a hydrolysable ester linkage for drug delivery as a "Trojan Horse Strategy." It is a new therapeutic approach to combat microbial infection and to address the issue of multi drug resistance in Gram‐negative, nosocomial pathogen Pseudomonas aeruginosa . Pyochelin (Pch) is a catecholate type of phenolate siderophore produced and utilized by the pathogen P. aeruginosa to assimilate iron when colonizing the vertebrate host. Zingerone, is active component present in ginger, a dietary herb known for its anti‐virulent approach against P. aeruginosa . In the present study, zingerone was exploited to act as a good substitute for existing antibiotics, known to have developed resistance by most pathogens. Encouraging results were obtained by docking analysis of pyochelin‐zingerone conjugate with FptA, the outer membrane receptor of pyochelin. Conjugate also showed anti‐quorum sensing activity and also inhibited swimming, swarming, and twitching motilities as well as biofilm formation in vitro .